2018
DOI: 10.1016/j.atmosenv.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variance in BC mass measurements from a small marine engine: Influence of the instruments, fuels and loads

Abstract: Knowledge of black carbon (BC) emission factors from ships is important from human health and environmental perspectives. A study of instruments measuring BC and fuels typically used in marine operation was carried out on a small marine engine. Six analytical methods measured the BC emissions in the exhaust of the marine engine operated at two load points (25% and 75%) while burning one of three fuels: a distillate marine (DMA), a low sulfur, residual marine (RMB-30) and a high-sulfur residual marine (RMG-380)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…They quantified the response of AVL smoke meter, LII 300, Aethalometer and TOA relative to MSS (selected arbitrarily as the reference instrument). Table 3 compares the slope and intercept of the linear regression reported in Jiang et al (2018) with the corresponding values from the present study. As mentioned, the slopes and intercepts shown in Table 3 are based on the MSS mass concentrations being on the x-axis and the mass concentrations from other BC instruments on the y-axis (see Figure S3 in the supplementary information for more details).…”
Section: Comparison Of Bc Measurement Techniquesmentioning
confidence: 80%
See 2 more Smart Citations
“…They quantified the response of AVL smoke meter, LII 300, Aethalometer and TOA relative to MSS (selected arbitrarily as the reference instrument). Table 3 compares the slope and intercept of the linear regression reported in Jiang et al (2018) with the corresponding values from the present study. As mentioned, the slopes and intercepts shown in Table 3 are based on the MSS mass concentrations being on the x-axis and the mass concentrations from other BC instruments on the y-axis (see Figure S3 in the supplementary information for more details).…”
Section: Comparison Of Bc Measurement Techniquesmentioning
confidence: 80%
“…The results presented in the current study are compared with the results reported in Jiang et al (2018) with similar BC instruments used to collect sample from a 2-stroke ship engine. They quantified the response of AVL smoke meter, LII 300, Aethalometer and TOA relative to MSS (selected arbitrarily as the reference instrument).…”
Section: Comparison Of Bc Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the numerous correction algorithms for the Aethalometer (e.g., Arnott et al, 2005;Collaud Coen et al, 2010;Kirchstetter and Novakov, 2007;Saturno et al, 2017;Schmid et al, 2006;Virkkula et al, 2007;Weingartner et al, 2003), we do not evaluate these in the present work to limit the scope. In fact, the majority of our focus is the B1999 and V2005 corrections to TAP and CLAP.…”
Section: The Spot Change In the Clap Was Manually Performedmentioning
confidence: 99%
“…Consequently, various correction algorithms exist to minimize these biases, but they are often specific only to certain instruments. For example, some are applicable to the PSAP, CLAP, and TAP (e.g., Bond et al, 1999;Müller et al, 2014;Ogren, 2010;Virkkula, 2010;Virkkula et al, 2005), while others are applicable to the AETH (e.g., Arnott et al, 2005;Collaud Coen et al, 2010;Drinovec et al, 2017;Kirchstetter and Novakov, 2007;Schmid et al, 2006;Virkkula et al, 2007Virkkula et al, , 2015Weingartner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%